2018
DOI: 10.1108/jme-03-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

The effects of check-in check-out on the academic planning and behavior of African American males

Abstract: Purpose-The Check-in Check-out (CICO) program is a Tier II behavioral intervention that has received empirical support as an effective way to reduce problem behaviors (Hawken and amp; Horner, 2003; March and amp; Horner, 2002). The purpose of this study is to use an intervention that combined CICO with social skill instruction and academic planning with three African-American ninth-grade males identified with emotional and behavioral disorders. A concurrent baseline across participants design was used to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…For preliminary and influence analyses as well as investigating publication bias we averaged effect sizes and their associated standard errors within studies ( k = 32). During preliminary analyses, a Grubbs’ test revealed the effect size for Toms () was an outlier ( G = 4.53, p < 0.001). This effect size, g = 7.18, was more than two times the next highest effect size and included one dependent variable unique to the included studies (essentially a measure of how accurately students carried out steps of the intervention which is not consistent with aims of CICO).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For preliminary and influence analyses as well as investigating publication bias we averaged effect sizes and their associated standard errors within studies ( k = 32). During preliminary analyses, a Grubbs’ test revealed the effect size for Toms () was an outlier ( G = 4.53, p < 0.001). This effect size, g = 7.18, was more than two times the next highest effect size and included one dependent variable unique to the included studies (essentially a measure of how accurately students carried out steps of the intervention which is not consistent with aims of CICO).…”
Section: Resultsmentioning
confidence: 99%
“…For these two reasons, this study was dropped from further analyses. As Zelinsky and Shadish () noted, excluding a study such as Toms () necessarily reduces the overall effect. An additional Grubbs’ test revealed that the effect size for Stuart () was an outlier ( G = 2.95, p < 0.01); however, there did not appear to be justification for its removal.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, teachers may struggle to recognize and understand students' social/emotional needs and this can lead to punitive approaches toward student behaviors (Hamre & Pianta, 2005). Teachers are 2-3 times more likely to use behavioral approaches and suspensions to control inappropriate behaviors with children from marginalized communities (Monroe, 2006;Siwatu et al, 2015;Toms, 2013). When teachers resort to repetitive administrative discipline, their students fall further behind in class and are more likely to continue behaviors leading to poor long-term academic outcomes.…”
Section: Elementary School Childrenmentioning
confidence: 99%
“…Prior research has shown increased academic engagement and decreased levels of disruptive behavior with elementary-age Black learners (Miller et al, 2015). More specifically related to the hypothesis in the present investigation, Toms et al (2018) combined CICO with social-skills instruction and found improvements in academic planning and externalizing behavior at the high-school level for Black learners with an EBD classification from the school system (Toms et al, 2018).…”
mentioning
confidence: 56%